2019
DOI: 10.1007/s00213-018-5121-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical and molecular mechanisms underlying the retrieval-extinction effect

Abstract: Extinction within the reconsolidation window, or 'retrieval-extinction', has received much research interest as a possible technique for targeting the reconsolidation of maladaptive memories with a behavioural intervention. However, it remains to be determined whether the retrieval-extinction effect-a long-term reduction in fear behaviour, which appears resistant to spontaneous recovery, renewal and reinstatement-depends specifically on destabilisation of the original memory (the 'reconsolidationupdate' accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 189 publications
(301 reference statements)
0
32
0
Order By: Relevance
“…The reemergence of the CR following extinction has also been observed under other situations, such as spontaneous recovery and reinstatement (Bouton & Bolles, 1979;Haberlandt, Hamsher, & Kennedy, 1978;Harris, Jones, Bailey, & Westbrook, 2000;Pavlov, 1927;Quirk, 2002;Rauhut et al, 2001;Rescorla & Heth, 1975;Richardson, Duffield, Bailey, & Westbrook, 1999;Robbins, 1990;Schiller et al, 2008), supporting the idea that the original fear memory is preserved and that extinction represents the formation of a new inhibitory association rather than erasure of the original memory (Bouton et al, 2006;Haberlandt et al, 1978;Quirk, 2002;Robbins, 1990;Schiller et al, 2008). Since the expression of renewal appears to depend on several factors (Cahill & Milton, 2019;Chen, Wang, Wang, & Li, 2017;Goode & Maren, 2014), understanding how the re-emergence of fear could be controlled is of fundamental importance for anxiety disorders.…”
Section: Introductionmentioning
confidence: 77%
“…The reemergence of the CR following extinction has also been observed under other situations, such as spontaneous recovery and reinstatement (Bouton & Bolles, 1979;Haberlandt, Hamsher, & Kennedy, 1978;Harris, Jones, Bailey, & Westbrook, 2000;Pavlov, 1927;Quirk, 2002;Rauhut et al, 2001;Rescorla & Heth, 1975;Richardson, Duffield, Bailey, & Westbrook, 1999;Robbins, 1990;Schiller et al, 2008), supporting the idea that the original fear memory is preserved and that extinction represents the formation of a new inhibitory association rather than erasure of the original memory (Bouton et al, 2006;Haberlandt et al, 1978;Quirk, 2002;Robbins, 1990;Schiller et al, 2008). Since the expression of renewal appears to depend on several factors (Cahill & Milton, 2019;Chen, Wang, Wang, & Li, 2017;Goode & Maren, 2014), understanding how the re-emergence of fear could be controlled is of fundamental importance for anxiety disorders.…”
Section: Introductionmentioning
confidence: 77%
“…In addition, it has been reported that old as well as strong memories are usually more resistant to reconsolidation blockers than new and/or weak ones (Milekic and Alberini, 2002; Eisenberg and Dudai, 2004; Suzuki et al, 2004), suggesting that different reactivation protocols might be required to destabilize deep-rooted, robust memories. Extinction induction can also restrain memory reconsolidation (Pedreira and Maldonado, 2003; Suzuki et al, 2004) and although reconsolidation and extinction are dissociable and reciprocally exclusive processes (Merlo et al, 2014) they share several neurotransmitter systems and intracellular signaling pathways (Cahill and Milton, 2019) and also can influence each other. Indeed, phenomena involving extinction within the reconsolidation window, as well as reconsolidation of reactivated extinction memory, have been described (Monfils et al, 2009; Rossato et al, 2010).…”
Section: Memories Are Adaptable: the Reconsolidation Processmentioning
confidence: 99%
“…However, our knowledge about the neurochemical bases of reconsolidation is still incipient. Difficulties do not rely only on identifying brain regions and intracellular pathways that might be differentially required for additional learning or memory modification through reconsolidation but on the fact that several neurotransmitter systems and signaling cascades that seem to be involved in reconsolidation are also required for other retrieval-induced cognitive processes, such as extinction (revised in Cahill and Milton, 2019). For example, extinction and reconsolidation are NMDA-dependent processes (Suzuki et al, 2004) modulated by dopaminergic and endocannabinoid neurotransmission (Marsicano et al, 2002; Hikind and Maroun, 2008; Lee and Flavell, 2014; Rossato et al, 2015) that involve AMPA receptor trafficking (Kim et al, 2007; Rao-Ruiz et al, 2011), all of which directly or indirectly control synaptic plasticity.…”
Section: Memories Are Adaptable: the Reconsolidation Processmentioning
confidence: 99%
“…Studies showing that the reminder-extinction procedure can prevent the return of threat responses have postulated that the reminder triggers a reconsolidation process, and extinction training during this reconsolidation window can overwrite the original threat memory 42 . Whether indeed the reminder-extinction depends specifically on disruption of the original memory remains to be determined 63 , and alternative explanations for the efficacy of the reminder-extinction procedures include active memory integration accounts 4 and the enhanced-extinction account 64 .…”
Section: Introductionmentioning
confidence: 99%